The Influence of Financial Performance, Firm Size, and Sales Growth on Firm Value (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
The food and beverage industry are generally known for its stability. Nevertheless, this sub-sector underwent fluctuations as a result of the COVID-19 pandemic, one of which was in its firm value. The study investigates how firm value is affected by key organizational characteristics, including financial performance, the scale of the firm, and the rate of sales growth. A firm's value is measured by its PBV (Price to Book Value). The study's measure of financial performance is a combination of Return on Equity (ROE) and the CR, DER, and TATO ratios. This study uses a quantitative approach. The study's population is composed of F&B firms publicly traded on the Indonesia Stock Exchange throughout 2019–2023. A purposive sampling technique was used to select the sample based on predefined requirements, leading to a total of 125 samples from 25 companies. Data were processed using WarpPLS version 8.0 to evaluate the research model through model fit, structural testing, and hypothesis testing. The results show that the model meets the required fit indices and has strong explanatory power. The findings reveal that profitability (ROE) and leverage (DER) have a positive and significant effect on firm value, while liquidity (CR) and sales growth exert a negative and significant effect. On the other hand, activity ratio (TATO) and firm size do not significantly influence firm value.